Laparoendoscopic single-site transvesical removal of mid-urethral polypropylene sling eroded into the bladder - Marek Roslan; Marcin Markuszewski; Artur Gibas; Wojciech Piaskowski; Kazimierz Krajka (Videosurgery and Other Miniinvasive Techniques)
Complications of mid-urethral sling procedure such as erosion into the bladder are not very common. However, whenthey occur, removal of the tape may be necessary. To date, this complication has usually been managed by retropubicexploration or operative cystoscopy, which can often be associated with disproportionate morbidity or even failure. Wepresent 2 cases of a laparoendoscopic single-site surgery (LESS) approach for removal of polypropylene tape erodedinto the bladder. We report two female patients aged 41 years and 47 years who underwent treatment with this noveltechnique. A TriPort® single-site access system was placed through the apex of the bladder under cystoscopic control.Carbon dioxide was used for insufflations of the bladder. A combination of straight and articulating laparoscopic instrumentswas used to dissect and completely remove the foreign body. Both patients were managed adequately in themanner presented above. The length of the skin incision was 20 mm. Time of intervention was 35 min and 40 min.No blood loss or complications occurred. A Foley 18 F catheter was left for seven days and the patients were dischargedon the 1st postoperative day. The follow-up period (4 months and 7 months) showed no events related to the method.Removal of foreign bodies of the bladder through a single transvesical laparoscopic port is technically feasible. This procedureoffers excellent visualization inside the bladder, especially near the bladder neck where polypropylene tapesoften reside, and provides patients with a minimally invasive approach through a single small incision.